2021
DOI: 10.3390/ani11092568
|View full text |Cite
|
Sign up to set email alerts
|

Mealworm (Tenebrio molitor): Potential and Challenges to Promote Circular Economy

Abstract: Over the last few years, the concept of Circular Economy (CE) has received a lot of attention due to its potential contribution to the Sustainable Development Goals (SDGs), especially by reconciling economic growth with the protection of the environment through its grow-make-use-restore approach. The use of insects in circular production systems has been a good example of this concept as insects can transform a wide range of organic waste and by-products into nutritious feedstuffs, which then go back into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 127 publications
(150 reference statements)
0
14
0
Order By: Relevance
“…Undoubtedly, this sector is gaining momentum, and its potential relies not only on food and feed, but also on the context of a circular economy. In particular, insects have the potential to convert a wide range of organic byproducts into food and feedstuffs, which then go back into the production cycle [51]. However, due to the current lack of evidence related to the safety of the final products, EU regulations still prohibit the use of waste products as a substrate for growing edible insects.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Undoubtedly, this sector is gaining momentum, and its potential relies not only on food and feed, but also on the context of a circular economy. In particular, insects have the potential to convert a wide range of organic byproducts into food and feedstuffs, which then go back into the production cycle [51]. However, due to the current lack of evidence related to the safety of the final products, EU regulations still prohibit the use of waste products as a substrate for growing edible insects.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…First, standard procedures in the insect production system for rearing, processing, and storage should be established to supply the insects as feed ingredients for pigs by mass production. The standard procedure for the mass production of insects should control the critical hazard point of food safety for consumers and livestock animals [ 5 , 47 ]. In addition to this, developing a processing method to make a novel insect product would give a superior value to the insect [ 28 ].…”
Section: Challenges In the Use Of Insect As A Feed Ingredientmentioning
confidence: 99%
“…Studies have reported that insects could be utilized as a valuable nutrient instead of expensive feedstuff ingredients which could lead to the evolution of the agricultural economy ( 4 7 ). Mealworm is one of the most attractive insect species used as an alternative and sustainable feed source ( 8 ). Frass is a term referring to insect larvae excreta, which includes larval excrement, heterogeneous, exoskeleton sheds, and residual feed ingredients along with abundant nutrients, beneficial microbes, and chitin ( 4 , 8 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mealworm is one of the most attractive insect species used as an alternative and sustainable feed source ( 8 ). Frass is a term referring to insect larvae excreta, which includes larval excrement, heterogeneous, exoskeleton sheds, and residual feed ingredients along with abundant nutrients, beneficial microbes, and chitin ( 4 , 8 10 ). Frass is a good source of palmitic, myristic, and stearic acids which are defined as saturated fatty acids characterized by Benzertiha et al ( 11 ) and Costa et al ( 12 ).…”
Section: Introductionmentioning
confidence: 99%